ARE ABDOMINAL PAIN AND DISTENTION SYMPTOMS OF BREAST CANCER? - Sadullah Girgin; Akın Önder; Murat Kapan; Uğur Fırat; Zülfü Arıkanoğlu; Mehmet Küçüköner (European Journal of Breast Health, 2012)

(untitled)
Breast cancer usually metastasizes to bone, lungs, liver and central nervous system. Rarely, atypical metastases may occur. Isolated peritoneal metastasis of breast cancer is very uncommon. On systemic examination of a 50-yearold woman who presented to our outpatients’ clinic with the complaints of abdominal pain and distention, abdominal ascites and a breast mass were found. Biopsy from the breast mass revealed invasive ductal carcinoma and laparoscopic peritoneal biopsy showed peritoneal metastasis of the breast cancer. Palliative chemotherapy was planned. The patient rejected the treatment and has been under follow-up for 6 months does not have any other metastasis now.